2015
DOI: 10.1021/acs.jnatprod.5b00118
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of 5-Hydroxy-2-(2-phenylethyl)chromone (5-HPEC) and Its Analogues as Non-nitrogenous 5-HT2B Ligands

Abstract: The involvement of the neurotransmitter serotonin (5-HT) in numerous physiological functions is often attributed to the diversity of receptors with which it interacts. Ligands targeting serotonin receptor 2B (5-HT2B) have received renewed interest for their potential to help understand the role of 5-HT2B in migraines, drug abuse, neurodegenerative diseases, and irritable bowel syndrome. To date, most of the ligands targeting 5-HT2B have been nitrogen-containing compounds. The natural product 5-hydroxy-2-(2-phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…5-HPEC showed selectivity for the 5-HT 2B R over other 5-HT 2 Rs. A subsequent SAR study on a series of synthesized and 5-HPEC's natural analogs was performed and showed that the most potent analog, 5-hydroxy-2-(2phenylpropyl)chromone (5-HPPC) (24, Figure 7), exhibited a 10-fold improvement in the 5-HT 2B R affinity (K i = 251 nM) and was able to maintain the 5-HT 2B R antagonism [139]. Recently, further optimization of 5-HPPC guided by molecular modeling approaches helped to identify 5-hydroxy-2-(3-(3-cyanophenyl)propyl)chromone (5-HCPC) (25, Figure 7), which exhibited an improved binding affinity (K i = 79 nM) compared with 5-HPPC and maintained inhibitory activity (IC 50 = 6310 nM in calcium flux assay) at the 5-HT 2B R, as well as selectivity over the 5-HT 2A R and the 5-HT 2C R [140].…”
Section: Chromone Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…5-HPEC showed selectivity for the 5-HT 2B R over other 5-HT 2 Rs. A subsequent SAR study on a series of synthesized and 5-HPEC's natural analogs was performed and showed that the most potent analog, 5-hydroxy-2-(2phenylpropyl)chromone (5-HPPC) (24, Figure 7), exhibited a 10-fold improvement in the 5-HT 2B R affinity (K i = 251 nM) and was able to maintain the 5-HT 2B R antagonism [139]. Recently, further optimization of 5-HPPC guided by molecular modeling approaches helped to identify 5-hydroxy-2-(3-(3-cyanophenyl)propyl)chromone (5-HCPC) (25, Figure 7), which exhibited an improved binding affinity (K i = 79 nM) compared with 5-HPPC and maintained inhibitory activity (IC 50 = 6310 nM in calcium flux assay) at the 5-HT 2B R, as well as selectivity over the 5-HT 2A R and the 5-HT 2C R [140].…”
Section: Chromone Derivativesmentioning
confidence: 99%
“…Figure 7. Representative chromone derivatives as non-nitrogenous 5-HT 2B R antagonists[138][139][140].…”
mentioning
confidence: 99%
“…Recently, chromones were described as an important scaffold for the development of novel 5-HT 2B ligands. Williams et al synthesized a chemical library inspired on the natural compound 2-(2-phenylethyl)­chromone (compound 10 , p K i = 5.6, Figure ) and screened it toward the 5-HT 2B receptor. Accordingly, 5-hydroxy-2-(2-phenylpropyl)­chromone (compound 11 , p K i = 6.6 at 5-HT 2B , Figure ) emerged as a potential 5-HT 2B ligand with potential therapeutic applicability on AD.…”
Section: Biological Interest Of Chromonesmentioning
confidence: 99%
“…Chromone-like compounds were found to be opioid ligands [13], but their analgesic activities have also been associated with other types of receptors [10,14]. Some could also potentially interact within the endogenous analgesia system by acting as serotonin receptor ligands [15,16]. Besides, these compounds are considered promising for pharmaceutical development because they possess low toxicity and are available in the human diet, due to their wide distribution among edible plants [17].…”
Section: Introductionmentioning
confidence: 99%